PENERAPAN MODEL PEMBELAJARAN MEAN-END-ANALYSIS DALAM MENINGKATKAN HASIL BELAJAR SISWA - Giawa, Kesayangan (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2024)
The background to the problem of this research is that student learning outcomes tend to be low. The research objectives are 1) To determine the application of the Mean-End-Analysis learning model in improving student learning outcomes in the Economics subject class X-IPS at SMA Negeri 1 Ulususua for the 2023/2024 academic year. 2) To determine the increase in student learning outcomes in the Economics subject class X-IPS at SMA Negeri 1 Ulususua for the 2023/2024 academic year. This type of research is Class Action (PTK). The subjects of this research were 20 students in class X-IPS. The research results showed that the evaluation results in cycle I, the average score was 60 with a completion percentage of only 40% and an incomplete percentage of 60%. Cycle II, there was an increase, the average score was 74.25 with a completion percentage of 100% and an incomplete percentage of 0%. The application of the Mean-End-Analysis learning model can foster students' enjoyment of lessons, foster and increase motivation in doing assignments, make it easier for students to understand lessons so as to achieve better learning outcomes. So it can be concluded that the application of the Mean-End-Analysis learning model can improve student learning outcomes in the Economics subject class X-IPS at SMA Negeri 1 Ulususua. The suggestions put forward by researchers are 1) For students, they should be more active in the learning process and independently carry out assignments given by the teacher without waiting for answers from their friends. 2) For teachers, Economics teachers should pay more attention to the suitability of the learning model used with the material being taught. 3) For schools, principals and teachers should always coordinate to create effective learning for students in an effort to improve student achievement and the quality of learning in schools.